A randomized trial testing deviant modeling, peer gender, and theft: replication and extension - Gallupe, Owen (Journal of experimental criminology, 2019)
Replicate previous experimental findings on the causal effect of deviant peer modeling and assess whether the gender of peer models is an important determinant of theft.